Optimalisasi Karang Taruna Desa Sooko Dalam Menjalankan Roda Keorganisasian - Mulyadi; Umi Lailatul M; Wahyu Andre I; Nurul Khomsatun (PUDAK: Local Wisdom Community Journal, 2022)
This mentoring program is carried out to optimize the Sooko Village youth group in running the organizational wheel. This optimization is manifested in two forms of assistance, namely assistance in carrying out activities and assistance in making accountability reports for an activity. This assistance uses the Asset Based Community Development (ABCD) method with 5 stages, namely define (determine), discovery (deep discovery), dream (dream), design (plan) and deliver (implement). The result of this assistance is that the youth organizations are able to carry out program activities optimally and are able to make accountability reports properly. This mentoring activity had a positive impact and brought benefits to the youth groups of Sooko village. This assisted activity can run well because of the support from various parties such as the village head, village officials, youth organizations and the surrounding community.